ANALISIS PERJALANAN WISATAWAN NUSANTARA: HUBUNGAN KARAKTERISTIK SOSIO DEMOGRAFI DENGAN MOTIVASI DAN PERILAKU PERJALANAN WISATA - , GITA OKTAVIA, Dra. Susi Daryanti, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Scientific study of population and travel patterns in the country have not been done many, meanwhile the available data are not detailed macro and have not been specified in giving an overview to its mechanism and activity process, therefore this study focuses more on the analysis to determine whether there is a relationship among socio-demographic characteristics of home tourists (Wisnus), travel motivation and travel behavior. The independent variables used in the study include socio-demographic characteristics of travelers consisting of a personal residence classification, gender, age, education, marital status, employment status, and type of job. Other independent variable is travel motivation and behavior which is used to look at what and how about their travel patterns, starting from the main intent to travel, whether to plan, type of tourist attraction visited and accommodation used. This study uses raw data, obtained from the Survey of Indonesia's population, conducted by the Badan Pusat Statistik (BPS). The analyzing data of the study used Nonparametric Statistical Chi-Square. The results showed that the socio-demographic characteristics are related to tourist travel behaviors. Average rate of men Wisnus to travel is 4.7 times a year , whereas women Wisnus is 2.4 times a year . Men Wisnus tend not to be overly concerned with the planning, in other words, they still planning but not having too detail, while women Wisnus are more detail in planning of schedule / time, cost breakdown, accommodation and tourist attractions to be visited . Men Wisnus tend to visit the sights of non-commercial outdoor activities which require much more power such as the mountains, natural caves and pristine beaches which have not been crowded and commercialized yet. They are whether more interested in visiting exhibition galleries if those are for commercial. Women Wisnus seem more attracted to indoor and commercial travel objects, such as dinning and shopping , as well as more interested in cultural tourism object if those are done outdoors . High school educated men Wisnus or lower prefer to visit family or friends to stay, while the D1 educated Wisnus or higher are more comfortable when staying at a hotel or commercial lodging . In contrast, high school educated women Wisnus or lower are more comfortable staying in commercial lodging, whereas D1 educated women Wisnus or higher tend to stay in their familiesâ place. The results showed that for high school educated Wisnus or lower prefer visiting natural ODTW whereas D1 educated Wisnus tend to pick up ODTW culture.